The risk of long-term cardiometabolic disease in women with premature or early menopause: A systematic review and meta-analysis - Liu, Jiajun; Jin, Xueshan; Liu, Wenbin; Chen, Wanying; Wang, Lan; Feng, Ziyi; Huang, Jieming (Frontiers in Cardiovascular Medicine, 2023)
Background: Transition into menopause is associated with an increased risk of cardiovascular disease (CVD). However, it is unclear whether the association exists between premature meno-pause (defined as age at menopause 40 years) or early menopause (defined as age at menopause 40–45 years) and CVD or cardiovascular risk factors. The aim of this review was to comprehen-sively evaluate and meta-analyze the most reliable evidence about the relationship between menopausal age and the risk of long-term cardiometabolic disease. Methods: A comprehensive literature search of the PubMed, Web of Science, and Embase data-bases from inception to October 1, 2022, for titles and abstracts with a restriction to English lan-guage papers led to the discovery of the studies. Data are expressed as the Hazard Ratio (HR) with 95% confidence intervals (CI). The degree of heterogeneity was measured using the I-square (I²) index. Results: 921,517 participants from 20 cohort studies published between 1998 and 2022 were considered. Compared to women with menopause at age >45 years, women with premature menopause (PM) or early menopause (EM) had a higher risks of type 2 diabetes (RR: 1.32, 95% CI: 1.08-1.62; RR: 1.11, 95% CI: 0.91-1.36,respectively), hyperlipidaemia (RR: 1.21, 95% CI: 1.05-1.39; RR: 1.17, 95% CI: 1.02-1.33, respectively), coronary heart disease (RR: 1.52, 95% CI: 1.22-1.91; RR: 1.19, 95% CI: 1.07-1.32, respectively), stroke (RR: 1.27, 95% CI: 1.02-1.58; RR: 1.13, 95% CI: 0.97-1.32, respectively) and total cardiovascular event (RR: 1.36, 95% CI: 1.16-1.60; RR: 1.14, 95% CI: 0.97-1.35, respectively). No difference was found for hypertension in PM or EM women. Additionally, we also found that PM women, but not EM women, were linked with an increased risk of ischemic and hemor-rhagic stroke. However, this is not in line with the conclusion that both PM and EM had a higher risk of total stroke. Conclusion: Women with PM or EM have a higher risk of developing long-term CVD, compared to normal age menopausal women. Therefore, we recommend early lifestyle interventions (e.g., maintaining a healthy lifestyle) and medical treatments (e.g., timely initiation of menopausal hormone therapy) to decrease the risk of cardiometabolic disease in early or premature meno-pausal women.